Auctions, Actions, and the Failure of Information Aggregation - Atakan, Alp E.; Ekmekci, Mehmet (American Economic Review, 2014)
We study a uniform-price auction where k identical common-value objects are allocated amongst z > k bidders who have imperfect signals about the state of the world. The common valuation is determined jointly by the state and an action that is chosen after winning an object. In large auctions, there are symmetric equilibria where the auction price aggregates no information. Moreover, market statistics other than price (e.g., the amount of rationing or the bid distribution) contain extra information about the state. In contrast, in standard large auctions without actions, the price aggregates all relevant information. (JEL D44, D82, D83)